2016
DOI: 10.21707/gs.v10.n02a02
|View full text |Cite
|
Sign up to set email alerts
|

Homegardens in north-eastern Portugal: former features, roles, gendered knowledge and practices

Abstract: Resumen -Este estudio describe las características de los huertos familiares en una zona rural protegida del nordeste de Portugal, el Parque Natural de Montesinho, Enfoca los roles fundamentales en la cultura local, recopilados con la ayuda de metodologías etnográficas durante tres años (2002 a 2005). Las relaciones de género y el modo como afectan el uso de los recursos y la gestión de los huertos también se discute: los antiguos huertos familiares eran dominios femeninos administrados de acuerdo a los valore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
1
5
0
3
Order By: Relevance
“…These results confirm similar findings of previous studies (Carvalho 2010;Carvalho & Morales 2013;Carvalho, 2016): within Portuguese rural contexts, that is, women and men agree as to the most common uses attributed to plants, but they differ about specific uses, such as in local traditional medicine and in rituals. Thus, while men and women plant knowledge are substantially overlapping, there are also female and male knowledge differences associated with their embodied experiences or "wayfaring" (Ingold 2011).…”
Section: Local Experts Gender Variability In Plant Categorizationsupporting
confidence: 92%
See 3 more Smart Citations
“…These results confirm similar findings of previous studies (Carvalho 2010;Carvalho & Morales 2013;Carvalho, 2016): within Portuguese rural contexts, that is, women and men agree as to the most common uses attributed to plants, but they differ about specific uses, such as in local traditional medicine and in rituals. Thus, while men and women plant knowledge are substantially overlapping, there are also female and male knowledge differences associated with their embodied experiences or "wayfaring" (Ingold 2011).…”
Section: Local Experts Gender Variability In Plant Categorizationsupporting
confidence: 92%
“…Evidence of different knowledge between women and men provides arguments to deconstruct the idea that rural societies are homogenous. It also raises awareness of the important role of women in the maintenance of local ecological knowledge, complementing studies carried out in Portugal (Carvalho 2016, Carvalho & Morales 2013 and other places (e.g. Kujawska et al 2017, Price 2006, Torres-Avilez et al 2016, Voeks 2007.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Overall the research region showed a lower species number in comparison to a wide variety of studies published from other parts of Europe. The number of food species was low in comparison to other areas in the wider Mediterranean and Caucasus (Carvalho 2016;Dolina et al 2017;Hajdari et al 2018;Kasper-Pakosz et al 2016;Korkmaz et al 2016;Mattalia et al 2020;Melián et al 2017;Mustafa et al 2020;Nedelcheva et al 2017;Oztürk et al 2018;Polat et al 2017;Pawera et al 2017;Pieroni and Cattero 2018;Pieroni andSõukand 2017, 2019;Pieroni 2017;Pieroni et al , 2020Savo et al 2019;Sõukand et al 2017Sõukand et al , 2019Sõukand et al , 2020Yeşil et al 2019), and the number of medicinal species also was lower than in comparative studies (Pieroni and Sõukand 2017;Nedelcheva et al 2017;Melián et al 2017;Sõukand et al-2017;Carvalho 2016;Polat et al 2017;Kasper-Pakosz et al 2016;Korkmaz et al 2016a;Dolina et al 2017, Korkmaz et al 2016bHajdari et al 2018;Oztürk et al 2018;Pawera et al 2017;Pieroni 2017;. The low variety of fungal species used as food was astonishing, especially when compared to other adjacent areas in Georgia, e.g.…”
Section: Discussionmentioning
confidence: 67%